ANDA-Evaluating Facilitated Feedback Enhancement - a Cluster randomised Trial (ANDA-EFFECT): protocol for a cluster randomised trial of audit feedback augmented with education and support, compared to feedback alone, on acceptability, utility and health outcomes in diabetes centres in Australia - Matthew Quigley; Arul Earnest; Sofianos Andrikopoulos; Natalie Wischer; Sally Green; Sophia Zoungas (Trials, 2022)
Abstract Background People living with diabetes must manage a range of factors for optimal control of glycaemia and to minimise the risk of diabetes-related complications. Diabetes practitioners are expected to follow guidelines for the key process of care and clinical outcomes, to help people living with diabetes achieve clinical targets. In Australia, the performance of diabetes centres against guidelines is evaluated by the Australian National Diabetes Audit, an annual clinical audit and feedback activity. Previous work has identified areas for improvement in the feedback provided to participating diabetes centres and suggested additional educational and support resources to assist in using audit feedback for the development of quality improvement activities. This cluster randomised trial will test the acceptability, utility and impact on selected clinical outcomes of the developed study intervention (audit feedback and a tailored educational and peer support cointervention). Methods Two-armed cluster randomised trial with Australian Diabetes Centres that participated in the Australian National Diabetes Audit in 2021 as the clusters, stratified by location and type of centre. We aim to recruit 35 diabetes centres in each arm. Both the intervention and control arms will receive an augmented feedback report, accompanied by a partially pre-populated slide deck. In addition, the intervention arm will receive a tailored theory-based intervention designed to address identified, modifiable barriers to utilising and implementing the recommendations from diabetes audit feedback. The co-primary outcomes are (1) HbA1c at the patient level, measured at 6 months after delivery of the intervention, and (2) the acceptability and utility of the augmented feedback and cointerventions at the practitioner level, measured at 3 months after delivery of the intervention. Discussion This trial aims to test the effects of systematic development and implementation of theory and evidence-informed changes to the audit feedback delivered to diabetes centres participating in an established national clinical diabetes audit. Potential benefits of improved audit feedback include more optimal engagement with the feedback by end clinical users which, ultimately, may lead to improvements in care for people living with diabetes. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN12621000765820. Prospectively registered on June 21, 2021